The spymaster of Baghdad: a true story of bravery, family, and patriotism in the battle against ISIS - Coker, Margaret (Dey St., 2021)
"From the former New York Times bureau chief in Baghdad comes the gripping and heroic story of an elite, top-secret team of unlikely spies who triumphed over ISIS"--